German Open Ended Real Estate Fund Performance – The Impact of Liquidity - Michael Stein (Credit and Capital Markets – Kredit und Kapital, 2013)
German Open Ended Real Estate Fund Performance – The Impact of Liquidity The liquidity crisis in the German Open-Ended Real Estate Funds (GOEREFs) industry was characterized by large outflows of money in several funds. Large and ongoing redemptions of fund shares held by both institutional and private / retail investors led to suspensions of redemptions, termination of funds and, ultimately, a new law. This study provides the most comprehensive overview of how the funds performed and how pronounced the differences between classes of funds in the exteuro80bn+ industry are. Using not only the net asset values of the funds as reported by the fund management companies, but the prices obtained at the secondary market when redemptions are suspended, indexes are constructed in order to provide a clear view of the performance of GOEREFs when the most relevant prices are used – those that may be achieved directly, rather than using book values. In this sense, the indexes provide a liquidity-corrected picture of fund returns. (G01, G10, G12) – – Performance deutscher offener Immobilienfonds: Auswirkung der Liquidität Die Liquiditätskrise der deutschen offenen Immobilienfonds war gekennzeichnet durch starke Abflüsse von Kapitale in vielen der Fonds. Anhaltende und teilweise hohe Rückgaben von Anteilscheinen durch institutionelle und private Investoren hat zu Aussetzungen von Anteilscheinrücknahmen, sowie der Auflösung von Fonds und letztendlich auch einer neuen Gesetzgebung geführt. Diese Studie gibt den wohl umfassendsten Überblick über die Wertentwicklung der Fonds und darüber wie unterschiedlich diese innerhalb der über 80 Millionen Euro schweren Branche war. Hierzu wird nicht nur auf den Net Asset Value, den KAG-Preis abgestellt, sondern auch auf die Preise welche am Zweitmarkt erzielt werden können wenn Anteilscheinrücknahmen ausgesetzt sind. Entsprechende Performance-Indices werden berechnet um ein klares Bild von der Wertentwicklung der Fonds zu erhalten wenn die tatsächlich relevanten Preise verwendet werden – jene welche direkt erzielt werden können, anstatt sich auf die Buchwerte zu beziehen. Somit erhält man eine Übersicht über die Rendite welche erzielt werden kann, wenn über den erzielbaren Preis bereits für die Liquidität korrigiert wurde. (G01, G10, G12)
Keywords: 330